Tantangan Penerapan Pajak Karbon di beberapa Negara: Kisah Sukses untuk Implementasi di Indonesia - Salsabila, Dwi (JURNAL ACITYA ARDANA, 2023)
Greenhouse gases are a threat to climate change that can have a negative impact on various aspects of life, one of which is the economy, Indonesia as a country that has committed to reducing greenhouse gas emissions in the Paris Agreement uses carbon taxes as a tool to fulfill this commitment. the first time Indonesia implemented a carbon tax, Indonesia needed to learn a lot from the countries that first implemented this policy. This study uses the Scoping review method which takes data from various international journals as well as real data from climatewatch. The results of this study the authors suggest that Indonesia apply a low rate at the beginning of the implementation of the carbon tax and begin to increase the rate over time and Indonesia can apply the redistribution of the carbon tax so that people's welfare does not decrease despite the implementation of this carbon tax.